Dental practice modification, protocol compliance and risk perception of dentists during COVID-19 pandemic in Colombia: a cross-sectional study - Barbosa-Liz, Diana M.; Agudelo-Suárez, Andrés Alonso; Tuesta-Mondragón, María Fernanda; Ariza-Olaya, Joaquín T.; Plaza-Ruíz, Sonia Patricia (Revista Facultad de Odontología Universidad de Antioquia, 2021)
Introduction: this study aimed to evaluate practice modification, use of personal protective equipment, biosafety measures, impact on career plans, prevalence of contagion, and risk perception of dentists during the COVID-19 pandemic 19 in Colombia. Methods: this is a cross-sectional study. Following ethical approval, an anonymous digital survey was conducted with dentists in Colombia. The questions comprised four domains: 1) sociodemographic, 2) employment and impact on career plans, 3) protocol compliance and biosafety, and 4) knowledge, risk, and contagion risk perception. A descriptive analysis of the data is presented. Results: 5,370 general and specialist dentists participated in the study (women: 3878; average age: 45 years). 41.94% were general dentists. Compliance with safety guidelines and use of personal protective equipment (PPE) was greater than 99%. The majority of dentists (91.29%) canceled their clinical activities during quarantine and have thought about reducing their working hours (77.96%). The perception of COVID-19 risk contagion was high (95.91% reported that contagion is likely/highly likely), although COVID-19 contagion self-report was low (0.61%). Conclusion: COVID-19 pandemic has strongly impacted the practice of dentistry in Colombia, leading to changes in clinical activities and career prospects. Biosafety measures compliance and PPE use was high. Although the contagion risk perception was high, self reported contagion was very low.